2013
DOI: 10.1007/s11258-013-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

Linking restoration outcomes with mechanism: the role of site preparation, fertilisation and revegetation timing relative to soil density and water content

Abstract: in Mediterranean southwestern Australia using two iconic tree species. Over the course of an entire growing season, our objectives were to: 1) characterise soil moisture profiles in relation to site preparation techniques (ripping and created ashbeds) and 2) determine whether early seedling establishment can be increased through site preparation techniques (ripping and ashbeds), plant treatments (various fertilisers and biochar) and early planting during the wet season. Ripping significantly reduced soil compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…(2012) and Ruthrof et al (2013a)], the key patterns of early survival, height and crown health as well as leaf water potential, stomatal conductance and soil respiration (at Yalgorup) were enhanced through the ripping of deep sandy soils. The addition of either fertiliser enhanced seedling growth, crown health and shoot growth and root biomass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2012) and Ruthrof et al (2013a)], the key patterns of early survival, height and crown health as well as leaf water potential, stomatal conductance and soil respiration (at Yalgorup) were enhanced through the ripping of deep sandy soils. The addition of either fertiliser enhanced seedling growth, crown health and shoot growth and root biomass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variation is much smaller in ripped plots compared with unripped plots (presumably ripping reduces heterogeneity within the soil profile). Previous work has shown that neither site is compacted; yet this technique alters moisture availability within the soil profile, promoting deeper root length and increasing revegetation success (Ruthrof et al 2013a). Root biomass did not differ significantly between ripping and control treatments; thus, root size and length is unlikely to explain greater seedling survival and vigour rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grant & Koch ), while other innovative work is being carried out by agencies and non‐profit groups to improve connectivity and the recovery of vegetation and faunal populations in degraded agricultural landscapes and large reserves (Jonson ; Ruthrof et al . , ; Legge et al . ; So et al .…”
Section: Introductionmentioning
confidence: 99%